Appearance evaluation of others' faces and bodies in anorexia nervosa and body dysmorphic disorder. Issue 2 (27th August 2016) - Moody, Teena D.; Shen, Vivian W.; Hutcheson, Nathan L.; Henretty, Jennifer R.; Sheen, Courtney L; Strober, Michael; Feusner, Jamie D.
ABSTRACT: Objective: Individuals with anorexia nervosa (AN) and body dysmorphic disorder (BDD) exhibit distorted perception and negative evaluations of their own appearance; however, little is known about how they perceive others' appearance, and whether or not the conditions share perceptual distortions. Method: Thirty participants with BDD, 22 with AN, now weight‐restored, and 39 healthy comparison participants (HC) rated photographs of others' faces and bodies on attractiveness, how overweight or underweight they were, and how much photographs triggered thoughts of their own appearance. We compared responses among groups by stimulus type and by level‐of‐detail (spatial frequency). Results: Compared to HCs, AN and BDD had lower attractiveness ratings for others' bodies and faces for high‐detail and low‐detail images, rated bodies as more overweight, and were more triggered to think of their own appearance for faces and bodies. In AN, symptom severity was associated with greater triggering of thoughts of own appearance and higher endorsement of overweight ratings for bodies. In BDD, symptom severity was associated with greater triggering of thoughts of own appearance for bodies and higher overweight ratings for low‐detail images. BDD was more triggered to think of own facial appearance than AN. Discussion: AN and BDD show similar behavioral phenotypes of negative appearance evaluations for others' faces and bodies, and have thoughts of their own appearance triggered even for images outside of their primary appearance concerns, suggesting a more complex cross‐disorder body‐image phenotype than previously assumed. Future treatment strategies may benefit from addressing how these individuals evaluate others in addition to themselves. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:127–138)